Genomic analysis of the population structure of Paenibacillus larvae in New Zealand - Binney, Barbara M.; Pragert, Hayley; Foxwell, Jonathan; Gias, Edna; Birrell, Meredith L.; Phiri, Bernard J.; Quinn, Oliver; Taylor, Michael; Ha, Hye Jeong; Hall, Richard J. (Frontiers in Microbiology, 2023)
New Zealand is a remote country in the South Pacific Ocean. The isolation and relatively late arrival of humans into New Zealand has meant there is a recorded history of the introduction of domestic species. Honey bees (Apis mellifera) were introduced to New Zealand in 1839, and the disease American foulbrood was subsequently found in the 1870s. Paenibacillus larvae, the causative agent of American foulbrood, has been genome sequenced in other countries. We sequenced the genomes of P. larvae obtained from 164 New Zealand apiaries where American foulbrood was identified in symptomatic hives during visual inspection. Multi-locus sequencing typing (MLST) revealed the dominant sequence type to be ST18, with this clonal cluster accounting for 90.2% of isolates. Only two other sequence types (with variants) were identified, ST5 and ST23. ST23 was only observed in the Otago area, whereas ST5 was limited to two geographically non-contiguous areas. The sequence types are all from the ERIC I genogroup. The ST18 and ST5 from New Zealand and international P. larvae all clustered by sequence type. Based on core genome MLST and SNP analysis, localised regional clusters were observed within New Zealand, but some closely related genomes were also geographically dispersed, presumably due to hive movements by beekeepers.